Metaphors for Environmental Sustainability: Redefining Our Relationship with Nature - Larson, Brendon (Yale University Press, 2011)
Scientists turn to metaphors to formulate and explain scientific concepts, but an ill-considered metaphor can lead to social misunderstandings and counterproductive policies, Brendon Larson observes in this stimulating book. He explores how metaphors can entangle scientific facts with social values and warns that, particularly in the environmental realm, incautious metaphors can reinforce prevailing values that are inconsistent with desirable sustainability outcomes. Metaphors for Environmental Sustainabilitydraws on four case studies-two from nineteenth-century evolutionary science, and two from contemporary biodiversity science-to reveal how metaphors may shape the possibility of sustainability. Arguing that scientists must assume greater responsibility for their metaphors, and that the rest of us must become more critically aware of them, the author urges more critical reflection on the social dimensions and implications of metaphors while offering practical suggestions for choosing among alternative scientific metaphors.